What limits a bystander’s action to perform cardiopulmonary resuscitation in China? Insights from a cross-sectional study conducted in Shaanxi Province - Dongdong Li; Kun Wang; Qiang Fu; Yan Li; Wangang Guo; Xiaolan Guo; Xin Zhang; Yuchan Hu; Liping Liao; Zhuoni Ma; Xin Chen; Miaomiao Cheng (Frontiers in Public Health, 2026)
Background Rate of bystander-initiated cardiopulmonary resuscitation (CPR) remains critically low in China. Identifying the underlying reasons may help reduce mortality from out-of-hospital cardiac arrest (OHCA). Methods A cross-sectional study was conducted among 572 participants in Shaanxi, China. A researcher-developed questionnaire was used to assess four domains: ability to recognize the need for CPR, willingness to perform CPR, internal concerns about initiating CPR, and actual CPR competence. Subgroup analyses were performed across demographic strata. Willingness and concerns regarding CPR for relatives versus strangers were distinguished and compared. Results Of the participants, 73.95% demonstrated the ability to recognize the need to perform CPR. Subgroup analysis revealed individuals aged ≥ 50 years, rural residents, and those with lower educational attainment had relatively poorer ability. Regarding willingness to perform CPR, over 94% of participants reported willingness to act for both relatives and strangers. However, the intensity was significantly greater for relatives than for strangers (8.84 ± 2.35 vs. 7.43 ± 2.53, p < 0.001). Notably, individuals with lower educational levels exhibited weaker willingness for both relatives and strangers. A high proportion of participants reported internal concerns about initiating CPR (91.78% for relatives, 93.88% for strangers), which was especially pronounced among spouses of high-risk patients. Lack of confidence in skills was the most frequently cited barrier. Additionally, participants reported more concerns regarding psychological fear, poor physical condition, medical litigation, and sanitary issues when the victim was a stranger. Finally, rural residents and those with primary education or below demonstrated poorer CPR knowledge scores. Conclusion Overall, the following issues should be prioritized. First, lack of confidence in skills—which may stem from poor actual competence—is widely cited. Second, individuals have greater concerns regarding psychological fear, poor physical condition, medical litigation, and sanitary issues when the victim is a stranger. Finally, special attention should be paid to populations characterized by age ≥ 50 years, lower educational level, and rural residence, as they demonstrated a tendency toward poorer performance across all assessed domains.